The Effect of Taxation System and Tax Audit on Tax Evasion - Prabowo, Kristianto Tricahya; Izzadieny, Fitra; Rizka, Nor Rahma (Jurnal Akuntansi, 2025)
This study was conducted to determine the effect of the taxation system and tax audits on tax evasion. Tax evasion is an act against tax law in Indonesia, so it needs to be controlled in various ways. This study obtained data by distributing questionnaires to 100 respondents with SPSS as the analysis tool. The results showed that the tax system and tax audit can reduce tax evasion